Optimizing ICMS Strategies for E-Commerce in Brazil: Tax Benefits and Profitability Insight - Almeida, Luís Fernando Correia e; Lima, Milena Moscardini Nabelice Guasti (EkBis: Jurnal Ekonomi dan Bisnis, 2024)
This study aimed to analyze the ICMS in the interstate operations of e-commerce companies, targeting non-taxpayers. The objective was to identify more economically advantageous strategies that would remain compliant with the tax legislation. The economic implications are evident in the use of tax benefits by various states, seeking to attract large companies to their jurisdictions through these incentives. A case study was conducted at a medium-sized company that has experienced significant growth in recent years, driven by both operational expansion and the rise of e-commerce on digital platforms. To carry out this case study, information from the company's tax documents was used, including verification of files and tax ledgers, and calculation of taxes and other reports relevant to the study. The analysis revealed that ICMS has a significant effect on the company's operations, necessitating the implementation of strategies to efficiently and legally reduce the tax burden. To implement these strategies, this study analyzed the tax benefits offered by specific states within the federation to this particular industry segment. By comparing these benefits to the company's operational values, opportunities to reduce the tax burden and increase profitability can be identified. The study demonstrated the potential for substantial cost savings by considering the company's location as the primary focus. These savings could range from 41.9% to 72.5%.